An Unbiased Flow Cytometry-Based Approach to Assess Subset-Specific Circulating Monocyte Activation and Cytokine Profile in Whole Blood - Kiefer, Jurij; Zeller, Johannes; Bogner, Balázs; Hörbrand, Isabel A.; Lang, Friederike; Deiss, Emil; Winninger, Oscar; Fricke, Mark; Kreuzaler, Sheena; Smudde, Eva; Huber-Lang, Markus; Peter, Karlheinz; et al. (Frontiers in Immunology, 2021)
Monocytes are the third most frequent type of leukocytes in humans, linking innate and adaptive immunity and are critical drivers in many inflammatory diseases. Based on the differential expression of surface antigens, three monocytic subpopulations have been suggested in humans and two in rats with varying inflammatory and phenotype characteristics. Potential intervention strategies that aim to manipulate these cells require an in-depth understanding of monocyte behavior under different conditions. However, monocytes are highly sensitive to their specific activation state and expression of surface markers, which can change during cell isolation and purification. Thus, there is an urgent need for an unbiased functional analysis of activation in monocyte subtypes, which is not affected by the isolation procedure. Here, we present a flow cytometry-based protocol for evaluating subset-specific activation and cytokine expression of circulating blood monocytes both in humans and rats using small whole blood samples (50 - 100 μL). In contrast to previously described monocyte isolation and flow cytometry visualization methods, the presented approach virtually leaves monocyte subsets in a resting state or fixes them in their current state and allows for an unbiased functional endpoint analysis without prior cell isolation. This protocol is a comprehensive tool for studying differential monocyte regulation in the inflammatory and allogeneic immune response in vitro and vivo.